PERAN KELOMPOK KERJA GURU (KKG) DALAM MENINGKATKAN PROFESIONAL GURU SAINS SEKOLAH DASAR KECAMATAN SURALAGA - Mijahamuddin Alwi (Universitas Hamzanwadi, 2009)
This study aims to describe roles of Teacher Work Group (TWG) as an organization to develop teachers’ professionalism, and its roles to improve science teachers’ professionalism. This study was a descriptive qualitative study. The data were collected through observations, interviews, and documents. The data trustworthiness in this study was established by using several steps including careful observations, triangulation, referential adequacy, and consultations with supervisors. The findings in this study reveal that TWG as an organization to develop teachers’ professionalism conducts a meeting once a week and the majority of the participants attend it in accordance with the schedule set before. In playing its roles, TWG actively takes part in responding to the problems that teachers face in Cluster 3 and the participants take an active part in joining the activities and in solving a variety of learning problems that they face. Besides, the roles of TWG in improving science teachers’ professionalism in Cluster 3, the main focus in the TWG activities, are on the aspects directly related to the learning quality improvement such as understanding of the curriculum, mastery of materials, use of instructional media, and use of evaluation methods and techniques. Meanwhile, aspects related to the development of teachers’ personality such as discipline in general and commitment to work do not become the main focus in the TWG activities. Keywords: Roles of Teacher Work Group